2018
DOI: 10.1186/s12889-018-5871-1
|View full text |Cite
|
Sign up to set email alerts
|

Current high prevalences of Strongyloides stercoralis and Opisthorchis viverrini infections in rural communities in northeast Thailand and associated risk factors

Abstract: BackgroundTwo important helminths, Strongyloides stercoralis (an intestinal roundworm) and Opisthorchis viverrini (a liver fluke), are endemic in northeast Thailand. There have been national campaigns in place aimed at the control and eradication of soil-transmitted helminthiasis and opisthorchiasis in Thailand for several decades. However, these helminths still exist and raise concerns regarding public health. This study aimed to evaluate the current prevalence of S. stercoralis and O. viverrini infections in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
7
18
3
Order By: Relevance
“…The seroprevalence in women was found to be significantly higher than that of men, which differs from other studies, where the prevalence was more frequent in males [31]. One possible explanation for this is the large contribution of Bolivian women to the population tested in our dataset, which have a high seroprevalence.…”
Section: Discussioncontrasting
confidence: 99%
“…The seroprevalence in women was found to be significantly higher than that of men, which differs from other studies, where the prevalence was more frequent in males [31]. One possible explanation for this is the large contribution of Bolivian women to the population tested in our dataset, which have a high seroprevalence.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study demonstrated a significant association between male sex and STH infection. Males had a higher prevalence of STH infections than females, consistent with previous studies in Thailand [10,29]. We found that males were 1.85 times more likely to be infected with STHs than females.…”
Section: Discussionsupporting
confidence: 91%
“…Seroprevalence in women was found to be significantly higher compared to men which differ from other studies where the prevalence was more frequent in males [32]. In our population data-base some countries like Bolivia with a high seroprevalence have a larger proportion of women.…”
Section: Discussioncontrasting
confidence: 84%